2012
DOI: 10.5194/acp-12-10405-2012
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime Arctic Ocean sea water properties and primary marine aerosol concentrations

Abstract: Abstract. Sea spray aerosols are an important part of the climate system through their direct and indirect effects. Due to the diminishing sea ice, the Arctic Ocean is one of the most rapidly changing sea spray aerosol source areas. However, the influence of these changes on primary particle production is not known.In laboratory experiments we examined the influence of Arctic Ocean water temperature, salinity, and oxygen saturation on primary particle concentration characteristics. Sea water temperature was id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 63 publications
5
60
4
Order By: Relevance
“…One main finding of the Zábori et al (2012a) study was that the marine particle number concentration decreased by at least four times with an increase in water temperature from −1 • C to about 6 • C. For higher water temperatures (upper measurement limit was 9 • C), the particle number concentration remained relatively constant. In this study we will examine if the trend found by Zábori et al (2012a) is consistent with measurements conducted using Arctic Ocean water at higher water temperatures, sampled during summertime, despite an expected higher biological activity during the polar day period (Hodal et al, 2012). To this end, the dependency of the total particle number concentration and number size distribution on the water temperature, for the same temperature range, is compared for summer-and wintertime measurements.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…One main finding of the Zábori et al (2012a) study was that the marine particle number concentration decreased by at least four times with an increase in water temperature from −1 • C to about 6 • C. For higher water temperatures (upper measurement limit was 9 • C), the particle number concentration remained relatively constant. In this study we will examine if the trend found by Zábori et al (2012a) is consistent with measurements conducted using Arctic Ocean water at higher water temperatures, sampled during summertime, despite an expected higher biological activity during the polar day period (Hodal et al, 2012). To this end, the dependency of the total particle number concentration and number size distribution on the water temperature, for the same temperature range, is compared for summer-and wintertime measurements.…”
Section: Introductionmentioning
confidence: 77%
“…Zábori et al, 2012a for winter experiments). Nevertheless some differences in water flow and dilution rate by clean air occurred.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations